Ustad Abdul Somad's Thoughts on the Islamic Brotherhood Trilogy - Muna, Rifatul; Sa'adah, Naili; Abdillah, Muhammad Nur Huda; Arifin, Wahidah Nur; Hidayati, Ardhia Intan; Cahyaningsih, Kurniati Agil; Fadilah, Adinda Suci; Tsani, Tsarifah (International Tatho Academics, 2025)
The purpose of this research is to explore Ustadz Abdul Somad's views on strengthening the Islamic brotherhood trilogy. This research method uses qualitative methods in the form of media observation studies using a content analysis approach. The results of the study concluded that in Ustad Abdul Somad's view, strengthening the Islamic brotherhood trilogy can be manifested through strengthening the value of Ukhuwah Islamiyah by strengthening the integration of the social life of Muslims for mutual understanding and help. Then, strengthening the value of Ukhuwah Wathaniyah which emphasises national unity in the midst of diversity. Furthermore, strengthening the value of Ukhuwah Basyariyah in the form of promoting universal humanitarian solidarity amid the social diversity of mankind. This research confirms that the trilogy of Islamic brotherhood can be a paradigmatic basis in realising a life of harmony amid the social plurality of humanity.